2014
DOI: 10.4049/jimmunol.1202797
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Are Required for Dendritic Cell–Based Immunotherapy at the Time of Tumor Challenge

Abstract: Increasing evidence suggests that NK cells act to promote effective T cell–based antitumor responses. Using the B16-OVA melanoma model and an optimized Gram-positive bacteria–dendritic cell (DC) vaccination strategy, we determined that in vivo depletion of NK cells at time of tumor challenge abolished the benefit of DC immunotherapy. The contribution of NK cells to DC immunotherapy was dependent on tumor Ag presentation by DC, suggesting that NK cells act as helper cells to prime or reactivate tumor-specific T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 58 publications
(88 reference statements)
2
39
1
Order By: Relevance
“…55 This innate cross talk can further impact adaptive responses, as evidenced by the reduced benefit of DC vaccination after NK cell depletion in a melanoma mouse model. 56 Both soluble (IFN-g) as well as contact-dependent (OX40-OX40L) factors contribute to NK cell-DC immune orchestration. These interactions may underlie the increased cytokine production and degranulation capacity we observe in BRGSF mice.…”
Section: Discussionmentioning
confidence: 99%
“…55 This innate cross talk can further impact adaptive responses, as evidenced by the reduced benefit of DC vaccination after NK cell depletion in a melanoma mouse model. 56 Both soluble (IFN-g) as well as contact-dependent (OX40-OX40L) factors contribute to NK cell-DC immune orchestration. These interactions may underlie the increased cytokine production and degranulation capacity we observe in BRGSF mice.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression and dysfunction of NK cell receptors has been observed under HBV infection (57). Regarding activating receptors, liver biopsies from woodchucks infected with a hepatitis virus showed upregulation of NKp46 (58).…”
mentioning
confidence: 99%
“…Shimizu and Fujii demonstrated that bone-marrow-derived DC immunization generated long-term NK-dependent antitumor immunity in a mouse model of melanoma, and that the longlasting antitumor NK response required endogenous DC [39]. Bouwer et al reported also the important contribution of NK cells in B16 melanoma challenge and their helper role in enhancing antitumor immunity [40]. Morandi et al recently demonstrated the in vivo relevance of DC editing by NK cells in expanding cancer-specific cytotoxic T lymphocytes (CTLs) in a TS/A mouse model of mammary adenocarcinoma.…”
Section: Enhancing Nk-dc Crosstalk In Cancer Immunotherapymentioning
confidence: 95%